The Effect of Using Various Magnetic Materials on Diesel Engines using Biodiesel Fuel - Aguk Zuhdi Muhammad Fathallah; Adhi Iswantoro; Hafiz N. H. Perdana (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2020)
One of method to improve engine performance and reduce fuel consumption is to use exposure to magnetic fields in the fuel lines. Several studies have proven that magnetic field exposure can improve diesel engine performance. This research aims to test the performance of a diesel engine using fuels that are given a magnetic field from 3 types of permanent magnets, namely magnets made from Neodymium Iron Boron (NdFeB), Aluminum Nickel Cobalt (AlNiCo), and Ferrite (Fe). Performance tests on the Yanmar TF85MH diesel engine include power and torque. The fuel used in this research is Biodiesel B20. The results showed that neodymium magnets (NdFeB) are the best magnets of the 3 types of magnets tested with an average increase in power of 2.30%, an average increase in torque of 2.35%.